ANALISIS PERBANDINGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN VARIABLE COSTING UMKM DI ACEH BESAR - Arumdalu, Ninda; Priantana, Riha Dedi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aimed to investigate the difference between the full costing method and the variable costing method in calculating the cost of production of some MSMEs products sold in Aceh Besar. The type of research is qualitative research with a descriptive approach. The subject of this research is two types of MSMEs that are engaged in handicrafts and food processing, known as Tahu Bang Lam, Tahu Garot, Galery Polem Awee, and Raga Tanyo. The data analysis method in this research is descriptive qualitative. The research data were obtained from interviews with MSMEs owners directly. The result of this study showed that the calculations of the cost of production by using full costing and variable costing methods are different. The full costing method generates a higher selling price than the variable costing method. Furthermore, the full costing method is easier to understand than the variable costing method, since many MSMEs still struggle to identify fixed and variable factory overhead costs.